Rancang Bangun Aplikasi Website Desa Untuk Pelayanan Publik (Studi Kasus Desa Kwasen) - Ahmad Ahsam Rozaq (CV. Multi Kreasi Media, 2024)
Kwasen Village is one of the villages in Kesesi District, Pekalongan Regency which carries out public service activities in the form of administration every day.However, local village officials still use the manual method for the data collection process where residents come to the village hall after which their personaldata will be recorded and recorded by writing on paper notes. visit the village hall to carry out administrative activities which will take up their time.To overcome this problem, an information system is needed that can handle data storage and administrative activities in a timely manner that is effective enough.Making a web-based information system by relying on the JavaScript language and the nodeJs framework with the aim of providing convenience and a way out for residents and village officials so that data collection and administrative activities can be more efficient in terms of time and secure in filing.